Na+/H+ exchanger 1 (NHE-1) redox-regulated gene and intracellular target for the redox control of cell death sensitivity - Akram, S.; Pervaiz, Shazib; Clement, M. (Nova Science Publishers, Inc., 2011)
Cell number in a multi-cellular organism is constant but dynamic. Cells are constantly undergoing growth; dead cells are replaced by new ones. Redox regulation of cell death has seen a paradigm shift in recent times. From damaging and unwanted moieties, ROS are now being recognized as playing vital roles in various cellular processes. Various mechanisms of how ROS can affect cellular functions have been proposed. Evidence has grown in this poorly understood field and many signaltransducing proteins and transcription factors have been added to the list of "redoxsensitive" proteins. In addition to an altered intracellular milieu, changes in intracellular pH (pHi) can affect many cellular functions including metabolism, cell growth, cell mobility, and so on. Na+-H+ exchanger isoform 1 (NHE-1) is one of the several transport proteins within the cell membrane which are specialized to actively transport acids and bases across the membrane. NHE-1 has been shown to be important in a wide range of cellular functions ranging from ischemia-reperfusion injury in myocardium to providing survival advantage in cancer cells. Evidence suggests that NHE1 activation at both transcription and protein level plays an important role in regulating its function. Although the concept of redox regulation of NHE-1 function was coined decades ago, it is only recently that increasing scientific evidence has renewed interest in this field. © 2011 Nova Scicence Publishers, Inc. All rights reserved.